Scratch self-repairing polycarbonate and preparation method thereof

By introducing bistriazinylamino homodiphenylethylene-disulfonic acid compound segments into polycarbonate molecules, the molecular structure is designed and modified to realize the scratch self-repair function of polycarbonate materials, the problem of poor scratch resistance performance of polycarbonate materials is solved, extending the service life and simplifying the preparation process.

CN119591858AActive Publication Date: 2025-03-11WANHUA CHEM GRP CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311157090.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-08
Publication Date
2025-03-11
Estimated Expiration
2043-09-08

AI Technical Summary

Technical Problem

The surface scratch resistance of polycarbonate materials is poor, making it difficult to avoid mechanical scratches during use, resulting in a short service life, especially in occasions where there are high requirements for the aesthetics and integrity of the product surface.

Method used

By introducing bistriazinylamino homodiphenylethylene-disulfonic acid compound segments into polycarbonate molecules, free radical polymerization of carbon-carbon double bonds is used to embed it into polycarbonate molecules, design and transform its molecular structure, introduce hydrogen bonds, coordination bonds, ionic bonds and triazinyl heterocyclic structures, and achieve self-healing through multiple dynamic reversible cross-linking.

Benefits of technology

The scratch self-repair function of polycarbonate materials is realized, and the problems of poor uniformity, high additive precipitation and secondary processing costs in traditional coating modification methods are solved, which extends the service life of the material, simplifies the preparation process, and is easy to achieve industrial continuous production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004438954100000021
    Figure BDA0004438954100000021
  • Figure BDA0004438954100000061
    Figure BDA0004438954100000061
  • Figure BDA0004438954100000081
    Figure BDA0004438954100000081
Patent Text Reader

Abstract

The invention provides scratch self-repairing polycarbonate and a preparation method thereof. The polycarbonate raw material contains a bis (triazinyl) amino-s-diphenylethylene-disulfonic acid compound. The method comprises the following steps: adding a bisphenol hydroxyl group-containing compound, alkali metal hydroxide and sodium hydrosulfite into water, and reacting to obtain a homogeneous aqueous solution a; adding a bis (triazinyl) amino-s-diphenylethylene-disulfonic acid compound into the aqueous solution a to obtain a homogeneous aqueous solution b; adding an oily solvent into the aqueous solution b to obtain a water-oil two-phase mixture c; phosgene and alkali liquor are introduced into the water-oil mixture c for a reaction, and a solution d is obtained; adding an end-capping reagent and a catalyst into the solution d, and continuously introducing alkali liquor to obtain a reaction product e; the reaction product e is subjected to standing two-phase separation, cleaning and solvent removal, and a PC-bis-triazinyl amino-s-diphenylethylene-disulfonic acid compound copolymerization solid product f is obtained. The polycarbonate provided by the invention has scratch self-repairing performance, and can realize integrity recovery of surface morphology in a short time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymer materials, and particularly relates to scratch self-repairing polycarbonate and a preparation method thereof. Background Art

[0002] Polycarbonate is a widely used thermoplastic engineering plastic, which is used in many fields such as automobiles, electronic devices, medical equipment, aerospace, construction, etc. As one of the five major engineering plastics, the demand for polycarbonate at home and abroad has been increasing in recent years.

[0003] Although the demand for polycarbonate is increasing year by year, its service life is not long due to its poor scratch resistance, low surface hardness, and difficulty in avoiding mechanical scratches during use. In some applications that require high surface aesthetics and integrity of products, such as mobile phone housings, display housings, and car interiors, the application of polycarbonate is limited. Therefore, it is very necessary to develop polycarbonate with scratch self-repairing function.

[0004] At present, there are relatively few studies on polycarbonate with scratch self-repairing function. The usual practice is to modify the surface of polycarbonate materials and add a surface coating. Patent CN111548731A adds a modified silica sol coating to the surface of polycarbonate, giving the coating room temperature self-repairing properties, but the coating is applied to the polycarbonate surface by spraying, and the spraying uniformity is difficult to ensure. The coating is not durable and is easy to fall off after long-term use; Patent CN110281613 discloses a method for preparing a polycarbonate plate with self-repairing function, and a coating with anti-fogging function is applied to the surface of the polycarbonate plate, but its preparation method is cumbersome and the coating is easy to fall off.

[0005] The method of adding a coating on the surface of the polycarbonate substrate to make polycarbonate have the function of scratch self-repairing is problematic. The coating lamination process has high requirements, which increases the cost; the uniformity of the coating is difficult to ensure; there is a risk of the coating falling off and failing after long-term use; and the addition of the coating causes the thickness of the polycarbonate to change, which limits its application in scenarios with high dimensional requirements. Summary of the invention

[0006] One of the purposes of the present invention is to provide a polycarbonate with scratch self-repairing function. The polycarbonate has stable molecular structure and chemical properties, good scratch self-repairing performance, simple preparation process, and easy to realize industrial continuous production.

[0007] In order to achieve the above-mentioned invention object and the above-mentioned technical effect, the present invention adopts the following technical scheme:

[0008] A scratch self-repairing polycarbonate, comprising the following structure:

[0009]

[0010] Wherein, R1 is a capping group, preferably a monophenol compound residue, and X is a C-containing 1-15 The N-containing group of the hydroxyalkyl group, n is an integer of 5-80.

[0011] In one embodiment of the present invention, in the polycarbonate, R1 is a residue of phenol and / or p-tert-butylphenol, and X is a C-containing 2-4 The NH of hydroxyalkyl contains 2 C 2-4 Hydroxylalkyl N, C 2-4 Hydroxyalkyl and C 1-10 One or more of the N of the alkyl group.

[0012] The present invention allows the bistriazine aminostilbene-disulfonic acid compound to undergo a polycondensation reaction with phosgene and a compound containing a bisphenol hydroxyl group during the polymerization process, and relies on the free radical polymerization of carbon-carbon double bonds to embed the bistriazine aminostilbene-disulfonic acid compound chain segment into the polycarbonate molecule, and designs and transforms the PC from the molecular structure. The molecular structure and chemical properties are stable, and the problems of poor uniformity, additive precipitation, and high secondary processing costs in the traditional film modification method can be solved. The bistriazine aminostilbene-disulfonic acid compound is connected to the polycarbonate molecule through a covalent bond, and hydrogen bonds, coordination bonds, ionic bonds, and triazine heterocyclic structures are introduced into the polycarbonate molecule. The hydrogen bonds, coordination bonds, ionic bonds, and shape memory effects are combined, and self-repair is achieved through multiple dynamic reversible crosslinking.

[0013] Another object of the present invention is to provide a method for preparing scratch self-repairing polycarbonate.

[0014] A method for preparing a self-healing polycarbonate, the method comprising the following steps:

[0015] S1: adding a compound containing bisphenol hydroxyl group, alkali metal hydroxide and hydrosulfite into water to react and obtain a homogeneous aqueous solution a;

[0016] S2: adding a bistriazine aminostilbene disulfonic acid compound to aqueous solution a to obtain a homogeneous aqueous solution b;

[0017] S3: adding an oily solvent to the aqueous solution b to obtain a water-oil two-phase mixture c;

[0018] S4: introducing phosgene and alkali solution into the water-oil mixture c to react and obtain solution d;

[0019] S5: adding a capping agent and a catalyst to solution d, and continuously passing an alkali solution to obtain a reaction product e;

[0020] S6: leaving the reaction product e to stand for two-phase separation, washing, and removing the solvent to obtain a PC-bistriazine aminostilbene-disulfonic acid compound copolymer solid product f;

[0021] Optionally, S7: the solid product f is placed in a high-temperature mold to obtain PC with scratch self-repairing function.

[0022] In one embodiment of the present invention, the bisphenol hydroxyl-containing compound in S1 is preferably bisphenol A and / or tetrabromobisphenol A; the alkali metal hydroxide is sodium hydroxide and / or potassium hydroxide; the sodium hydrosulfite is a strongly reducing sulfate, preferably sodium dithionite and / or sodium thiosulfate; preferably, the concentration of the bisphenol hydroxyl-containing compound in the aqueous solution a is 10-18wt%; preferably, the concentration of the alkali metal hydroxide in the aqueous solution a is 4-6wt%; preferably, the concentration of the sodium hydrosulfite in the aqueous solution a is 0.1-0.8wt%.

[0023] In one embodiment of the present invention, the reaction temperature of S1 is 20°C-40°C, preferably 30°C-37°C; the reaction time is 15-40 min; and the reaction is carried out under an inert gas atmosphere.

[0024] In one embodiment of the present invention, the molar ratio of the bistriazine aminostilbene-disulfonic acid compound described in S2 to the compound containing bisphenol hydroxyl group is (0.01-0.1):1;

[0025] In one embodiment of the present invention, the reaction temperature of S2 is 20°C-40°C, preferably 30°C-37°C; the reaction time is 10-30 min; and the reaction is carried out under an inert gas atmosphere.

[0026] In one embodiment of the present invention, the oil phase solvent in S3 is a chlorinated hydrocarbon, preferably one or more of dichloromethane, dichloroethane, trichloroethane, and tetrachloroethane; preferably, the mass ratio of the oily solvent to the aqueous solution a is (0.5-2):1, preferably (0.9-1.1):1.

[0027] In one embodiment of the present invention, the molar ratio of phosgene to the compound containing bisphenol hydroxyl group in S4 is (1.2-1.5):1.

[0028] In one embodiment of the present invention, the alkali in S4 is an alkaline hydroxide, preferably an alkali metal hydroxide, more preferably sodium hydroxide and / or potassium hydroxide; preferably, the concentration of the alkali solution is 10wt%-50wt%, preferably 25wt%-35wt%.

[0029] In one embodiment of the present invention, the temperature in S4 is 20-35°C and the reaction time is 5-30 min.

[0030] In one embodiment of the present invention, the end-capping agent in S5 is a monophenol compound, preferably phenol and / or p-tert-butylphenol; preferably, the molar ratio of the end-capping agent to the compound containing bisphenol hydroxyl group is (0.02-0.04):1.

[0031] In one embodiment of the present invention, the catalyst in S5 is a nitrogen compound that catalyzes interfacial polycondensation reaction, preferably one or more of triethylamine, N-ethylpiperidine, and N-isopropylpiperidine; preferably, the molar ratio of the catalyst to the compound containing bisphenol hydroxyl group is (0.002-0.004):1.

[0032] In one embodiment of the present invention, the alkali in S5 is an alkaline hydroxide, preferably an alkali metal hydroxide, more preferably sodium hydroxide and / or potassium hydroxide; preferably, the concentration of the alkali solution is 10wt%-50wt%, preferably 25wt%-35wt.

[0033] In one embodiment of the present invention, the temperature in S5 is 25-37° C., and the reaction time is 15-40 min.

[0034] In one embodiment of the present invention, the cleaning in S6 is pickling and water washing; preferably, a strong acid is used for pickling; preferably, the mass ratio of acid to oil phase during pickling is (0.1-0.5):1.

[0035] In one embodiment of the present invention, the catalyst content in the solid product e in S6 is less than 1 ppm, the chloride ion content is less than 20 ppm, and the oily solvent content is less than 200 ppm.

[0036] In one embodiment of the present invention, the mold temperature in S7 is 240° C.-360° C., and the insulation time is 10 min-180 min.

[0037] Another object of the present invention is to provide a use of scratch self-repairing polycarbonate.

[0038] A use of scratch self-repairing polycarbonate, wherein the polycarbonate is the above-mentioned polycarbonate, or is the polycarbonate prepared by the above-mentioned method, and the polycarbonate is used for polycarbonate products requiring scratch self-repairing, preferably for polycarbonate products in the fields of electronic products, automotive interiors, and optical lighting.

[0039] Compared with the prior art, the present invention has the following advantages and effects:

[0040] 1) The scratch self-healing polycarbonate material prepared by the present invention is designed and modified from the molecular structure of PC, and its molecular structure and chemical properties are stable, which can solve the problems of poor uniformity, precipitation of additives, and high secondary processing costs existing in traditional film modification methods.

[0041] 2) The polycarbonate of the present invention has a scratch self-repairing function, which can restore the scratched part of the polycarbonate product to its original state, prolonging the service life of the polycarbonate material and greatly improving its application value;

[0042] 3) The scratch self-repairing polycarbonate preparation method of the present invention is simple, easy to operate, and easy to realize industrial continuous production. DETAILED DESCRIPTION

[0043] The technical solution of the present invention is described in detail below in conjunction with the preferred implementation. The embodiments of the present invention are only used as an illustration of the present invention and do not limit the scope of the present invention. Raw materials used in the experiment:

[0044] Bisphenol A: industrial grade, purchased from Changchun Chemical Industry;

[0045] Tetrabromobisphenol A: industrial grade, purchased from Changchun Chemical Industry;

[0046] Bistriazineaminostilbene-disulfonic acid compound: analytical grade, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0047] Sodium hydroxide: analytical grade, purchased from Tianjin Kemeiou Chemical Reagent Co., Ltd.;

[0048] Potassium hydroxide: analytical grade, purchased from Tianjin Kemeiou Chemical Reagent Co., Ltd.;

[0049] Sodium hydrosulfite: industrial grade, purchased from Shanghai Myrel Chemical Technology Co., Ltd.

[0050] Phosgene: industrial grade, Wanhua Chemical;

[0051] Dichloromethane: analytical grade, purchased from Beijing Inokai Chemical Reagent Co., Ltd.;

[0052] Ethylene dichloride: analytical grade, purchased from Beijing Inokai Chemical Reagent Co., Ltd.;

[0053] Triethylamine: analytical grade, purchased from Tianjin Komiou Technology Co., Ltd.;

[0054] p-tert-Butylphenol: purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0055] Pure water: industrial grade, Wanhua Chemical.

[0056] The NMR was performed using an AvⅢ nuclear magnetic resonance spectrometer from Bruker, Switzerland, with deuterated chloroform as solvent.

[0057] The glossiness of the polycarbonate surface was measured using a micro gloss meter to characterize its self-repair rate. The specific implementation is as follows: Place the polycarbonate test piece on a horizontal table to measure the initial gloss of the surface A0, then use 0000# steel wool to scratch the polycarbonate surface horizontally and vertically 10 times each, then measure the gloss A1 when the surface is damaged, then let it stand at room temperature for 2 hours, and then measure the gloss A2 after the surface is repaired. The scratch repair rate of the polycarbonate surface is: (A2-A1) / (A0-A1)×100%.

[0058] Example 1

[0059] Under a nitrogen atmosphere, 1000 g of deionized water was added to a 5 L jacketed flask, and then 116.4 g of bisphenol A solid, 46.6 g of sodium hydroxide solid and 1.16 g of sodium dithionite were added thereto, the temperature was set to 30° C., stirring was started, the stirring speed was set to 300 rpm, and stirring was performed for 30 minutes until the solid was completely dissolved to obtain a homogeneous aqueous solution;

[0060] 2.97 g of bistriazine aminostilbene-disulfonic acid compound was added to the homogeneous aqueous solution, the structural formula of which is as follows:

[0061]

[0062] Set the temperature to 30°C, start stirring, set the stirring speed to 300 rpm, and stir for 15 minutes to obtain a homogeneous aqueous solution;

[0063] Add 582 g of dichloromethane to the homogeneous aqueous solution to obtain a water-oil two-phase mixture;

[0064] The temperature was adjusted to 20° C., stirring was started, the stirring speed was set to 300 rpm, 60.65 g of gaseous phosgene was introduced into the flask at a rate of 6 g / min, and a 25 wt % sodium hydroxide solution was introduced into the flask at a rate of 6 g / min. The reaction was stopped after 5 minutes to obtain an intermediate product solution;

[0065] The temperature was adjusted to 25° C., stirring was started, and the stirring speed was set to 300 rpm. While stirring, 1.53 g of p-tert-butylphenol and 0.10 g of triethylamine were added to the intermediate product solution, and a 25 wt % sodium hydroxide solution was continuously introduced at a rate of 0.5 g / min. The reaction was stopped after 15 minutes to obtain a final reaction product.

[0066] The reaction product was allowed to stand for oil-water separation. The oil phase was first washed with 58.2 g of a 1 wt% hydrochloric acid solution and then washed with 700 g of deionized water. The dichloromethane in the oil phase was then removed to obtain a PC-bistriazineaminobenzene-disulfonic acid compound copolymer solid product having a catalyst content of 0.21 ppm, a chloride ion content of 12 ppm, and an oily solvent content of 54 ppm.

[0067] Single chain segment 1 H NMR (CDCl3, 500MHZ): δ1.35 (s, 18H), 1.72 (s, 24H), 2.00 (s, 2H), 3.57 (m, 4H), 4.00 (m, 4H), 4.56 (t, J=17.3Hz, 4H), 7.05 (s, 2H), 7.12 (s , 2H), 7.21 (d, J=8.2Hz, 20H), 7.27 (d, J=8.2Hz, 16H), 7.44 (m, 2H), 7.52 (d, J=8.2Hz, 2H), 7.53 (d, J=8.2Hz, 2H), 7.56 (d, J=7.7Hz, 4H).

[0068] The solid product was placed in a flat vulcanizer, the temperature was set to 240°C, the insulation time was 10 min, and a PC test piece with a thickness of 3 mm was obtained.

[0069] The scratch self-repair rate of the polycarbonate surface tested using a micro-gloss meter was 87.5%.

[0070] Example 2

[0071] Under a nitrogen atmosphere, 1000 g of deionized water was added to a 5 L jacketed flask, and then 200 g of bisphenol A solid, 70 g of potassium hydroxide solid and 2 g of sodium dithionite were added thereto, the temperature was set to 33 ° C, stirring was started, the stirring speed was set to 300 rpm, and stirring was performed for 25 minutes until the solid was completely dissolved to obtain a homogeneous aqueous solution;

[0072] To the above homogeneous aqueous solution, 24.35 g of a bistriazine aminostilbene-disulfonic acid compound having the following structural formula was added:

[0073]

[0074] Set the temperature to 33°C, start stirring, set the stirring speed to 300 rpm, and stir for 20 minutes to obtain a homogeneous aqueous solution;

[0075] Add 1280 g of ethylene dichloride to the homogeneous aqueous solution to obtain a water-oil two-phase mixture;

[0076] The temperature was adjusted to 30° C., stirring was started, the stirring speed was set to 300 rpm, 113 g of gaseous phosgene was introduced into the flask at a rate of 6 g / min, and 30% potassium hydroxide solution was introduced into the flask at a rate of 6 g / min. The reaction was stopped after 20 minutes to obtain an intermediate product solution;

[0077] The temperature was adjusted to 30° C., stirring was started, and the stirring speed was set to 300 rpm. While stirring, 4 g of p-tert-butylphenol and 0.27 g of triethylamine were added to the intermediate product solution, and 30% potassium hydroxide solution was continuously introduced at a rate of 0.5 g / min. The reaction was stopped after 25 minutes to obtain a final reaction product.

[0078] The reaction product was allowed to stand for oil-water separation. The oil phase was first washed with 384 g of 1% hydrochloric acid solution and then with 700 g of deionized water. The dichloromethane in the oil phase was then removed to obtain a PC-bistriazineaminobenzene-disulfonic acid compound copolymer solid product having a catalyst content of 0.33 ppm, a chloride ion content of 11 ppm and an oily solvent content of 37 ppm.

[0079] Single chain segment 1 H NMR (CDCl3, 500MHZ): δ1.35 (s, 18H), 1.72 (s, 18H), 2.00 (s, 2H), 3.57 (m, 4H), 4.00 (m, 4H), 4.56 (t, J=17.3Hz, 4H), 7.05 (s, 2H), 7.12 (s , 2H), 7.21 (d, J=8.2Hz, 16H), 7.27 (d, J=8.2Hz, 12H), 7.44 (m, 2H), 7.52 (d, J=8.2Hz, 2H), 7.53 (d, J=8.2Hz, 2H), 7.56 (d, J=7.7Hz, 4H).

[0080] The solid product was placed in a flat vulcanizer, the temperature was set to 280°C, the heat preservation time was 60 min, and a PC test piece with a thickness of 3 mm was obtained.

[0081] The scratch self-repair rate of the polycarbonate surface tested using a micro-gloss meter was 91.6%.

[0082] Example 3

[0083] Under a nitrogen atmosphere, 1000 g of deionized water was added to a 5 L jacketed flask, and then 238 g of tetrabromobisphenol A solid, 79.37 g of sodium hydroxide solid and 5.29 g of sodium dithionite were added thereto, the temperature was set to 35 ° C, stirring was turned on, the stirring speed was set to 300 rpm, and stirring was performed for 30 minutes until the solid was completely dissolved to obtain a homogeneous aqueous solution;

[0084] To the above homogeneous aqueous solution, 25.54 g of a bistriazine aminostilbene-disulfonic acid compound having the following structural formula was added:

[0085]

[0086] Set the temperature to 35°C, start stirring, set the stirring speed to 300 rpm, and stir for 25 minutes to obtain a homogeneous aqueous solution;

[0087] Add 1984 g of dichloromethane to the homogeneous aqueous solution to obtain a water-oil two-phase mixture;

[0088] The temperature was adjusted to 35° C., stirring was started, the stirring speed was set to 300 rpm, 60.64 g of gaseous phosgene was introduced into the flask at a rate of 6 g / min, and 32% sodium hydroxide solution was introduced into the flask at a rate of 6 g / min. The reaction was stopped after 25 minutes to obtain an intermediate product solution;

[0089] The temperature was adjusted to 35° C., stirring was started, and the stirring speed was set to 300 rpm. While stirring, 2.63 g of p-tert-butylphenol and 0.18 g of triethylamine were added to the intermediate product solution, and 32% sodium hydroxide solution was continuously introduced at a rate of 0.5 g / min. The reaction was stopped after 30 minutes to obtain a final reaction product.

[0090] The reaction product was allowed to stand for oil-water separation. The oil phase was first washed with 992 g of 1% hydrochloric acid solution and then with 700 g of deionized water. The dichloromethane in the oil phase was then removed to obtain a PC-bistriazineaminobenzene-disulfonic acid compound copolymer solid product having a catalyst content of 0.37 ppm, a chloride ion content of 18 ppm and an oily solvent content of 49 ppm.

[0091] The solid product was placed in a flat vulcanizer, the temperature was set to 320°C, the insulation time was 120 min, and a PC test piece with a thickness of 3 mm was obtained.

[0092] The scratch self-repair rate of the polycarbonate surface tested using a micro-gloss meter was 95.3%.

[0093] Example 4

[0094] Under a nitrogen atmosphere, 1000 g of deionized water was added to a 5 L jacketed flask, and then 239.36 g of bisphenol A solid, 79.79 g of sodium hydroxide solid and 10.64 g of sodium dithionite were added thereto, the temperature was set to 37 ° C, stirring was turned on, the stirring speed was set to 300 rpm, and stirring was performed for 40 minutes until the solid was completely dissolved to obtain a homogeneous aqueous solution;

[0095] To the above homogeneous aqueous solution, 102.25 g of a bistriazine aminostilbene-disulfonic acid compound having the following structural formula was added:

[0096]

[0097] Set the temperature to 37°C, start stirring, set the stirring speed to 300 rpm, and stir for 30 minutes to obtain a homogeneous aqueous solution;

[0098] Add 2660 g of ethylene dichloride to the homogeneous aqueous solution to obtain a water-oil two-phase mixture;

[0099] The temperature was adjusted to 35° C., stirring was started, the stirring speed was set to 300 rpm, 155.90 g of gaseous phosgene was introduced into the flask at a rate of 6 g / min, and 35% sodium hydroxide solution was introduced into the flask at a rate of 6 g / min. The reaction was stopped after 30 minutes to obtain an intermediate product solution;

[0100] The temperature was adjusted to 37° C., stirring was started, and the stirring speed was set to 300 rpm. While stirring, 6.30 g of p-tert-butylphenol and 0.42 g of triethylamine were added to the intermediate product solution, and 35% sodium hydroxide solution was continuously introduced at a rate of 0.5 g / min. The reaction was stopped after 40 minutes to obtain a final reaction product.

[0101] The reaction product was allowed to stand for oil-water separation. The oil phase was first washed with 1330 g of 1% hydrochloric acid solution and then with 700 g of deionized water. The dichloroethane in the oil phase was then removed to obtain a PC-bistriazineaminobenzene-disulfonic acid compound copolymer solid product with a catalyst content of 0.41 ppm, a chloride ion content of 16 ppm and an oily solvent content of 29 ppm.

[0102] The solid product was placed in a flat vulcanizer, the temperature was set to 360°C, the holding time was 180 min, and a PC test piece with a thickness of 3 mm was obtained.

[0103] The scratch self-repair rate of the polycarbonate surface tested using a micro-gloss meter was 98.2%.

[0104] Comparative Example 1

[0105] Currently, the patents for the preparation of polycarbonate with scratch self-repairing function all use the traditional coating modification method, and there is no technical report on the chemical modification to embed the functional monomer into the polycarbonate chain segment through reaction. This comparative example is compared with the coating modification method.

[0106] First, a common polycarbonate test piece without special functional groups was prepared. The preparation method was the same as that of Example 1, except that the bistriazine aminostilbene-disulfonic acid compound was not added. The prepared polycarbonate test piece had a catalyst content of 0.35 ppm, a chloride ion content of 24 ppm, and an oily solvent content of 51 ppm.

[0107] The solid product was placed in a flat vulcanizer, the temperature was set to 320°C, the heat preservation time was 60 min, and a PC test piece with a thickness of 3 mm was obtained.

[0108] The scratch self-repairing coating was prepared according to the method described in Example 1 of patent CN111548731A, and the coating was sprayed on a 3 mm PC test piece.

[0109] The scratch self-repair rate of the polycarbonate surface tested using a micro-gloss meter was 77.3%.

Claims

1. A scratch self-repairing polycarbonate, characterized in that: The polycarbonate comprises the following structure: Wherein, R1 is a capping group, preferably a monophenol compound residue, and X is a C-containing 1-15 The N-containing group of the hydroxyalkyl group, n is an integer of 5-80.

2. The polycarbonate according to claim 1, characterized in that In the polycarbonate, R1 is a residue of phenol and / or p-tert-butylphenol, and X is a C-containing 2-4 The NH of hydroxyalkyl contains 2 C 2-4 Hydroxylalkyl N, C 2-4 Hydroxyalkyl and C 1-10 One or more of the N of the alkyl group.

3. A method for preparing the scratch self-repairing polycarbonate according to claim 1 or 2, characterized in that: The method comprises the following steps: S1: adding a compound containing bisphenol hydroxyl group, alkali metal hydroxide and hydrosulfite into water to react and obtain a homogeneous aqueous solution a; S2: adding a bistriazine aminostilbene disulfonic acid compound to aqueous solution a to obtain a homogeneous aqueous solution b; S3: adding an oily solvent to the aqueous solution b to obtain a water-oil two-phase mixture c; S4: introducing phosgene and alkali solution into the water-oil mixture c to react and obtain solution d; S5: adding a capping agent and a catalyst to solution d, and continuously passing an alkali solution to obtain a reaction product e; S6: leaving the reaction product e to stand for two-phase separation, washing, and removing the solvent to obtain a PC-bistriazine aminostilbene-disulfonic acid compound copolymer solid product f; Optionally, S7: the solid product f is placed in a high-temperature mold to obtain PC with scratch self-repairing function.

4. The method according to claim 3, characterized in that The bisphenol hydroxyl-containing compound in S1 is preferably bisphenol A and / or tetrabromobisphenol A; the alkali metal hydroxide is sodium hydroxide and / or potassium hydroxide; the hydrosulfite is a strong reducing sulfate, preferably sodium dithionite and / or sodium thiosulfate; Preferably, the concentration of the compound containing bisphenol hydroxyl group in the aqueous solution a is 10-18 wt %; Preferably, the concentration of the alkali metal hydroxide in the aqueous solution a is 4-6 wt %; Preferably, the concentration of the hydrosulfite in the aqueous solution a is 0.1-0.8wt%; And / or, the reaction temperature of S1 is 20°C-40°C, preferably 30°C-37°C; the reaction time is 15-40 min; and the reaction is carried out under an inert gas atmosphere.

5. The method according to claim 3, characterized in that: The molar ratio of the bistriazine aminostilbene-disulfonic acid compound to the bisphenol hydroxyl-containing compound in S2 is (0.01-0.1):1; And / or, the reaction temperature of S2 is 20°C-40°C, preferably 30°C-37°C; the reaction time is 10-30 min; and the reaction is carried out under an inert gas atmosphere.

6. The method according to claim 3, characterized in that S3 The oil phase solvent is a chlorinated hydrocarbon, preferably one or more of dichloromethane, dichloroethane, trichloroethane, and tetrachloroethane; Preferably, the mass ratio of the oily solvent to the aqueous solution a is (0.5-2):1, preferably (0.9-1.1):

1.

7. The method according to claim 3, characterized in that The molar ratio of phosgene to the compound containing bisphenol hydroxyl group in S4 is (1.2-1.5):1; And / or, the base in S4 is an alkaline hydroxide, preferably an alkali metal hydroxide, more preferably sodium hydroxide and / or potassium hydroxide; Preferably, the concentration of the alkali solution is 10wt%-50wt%, preferably 25wt%-35wt%; And / or, the temperature in S4 is 20-35° C., and the reaction time is 5-30 min.

8. The method according to claim 3, characterized in that The end-capping agent in S5 is a monophenol compound, preferably phenol and / or p-tert-butylphenol; Preferably, the molar ratio of the end-capping agent to the compound containing bisphenol hydroxyl group is (0.02-0.04):1; And / or, the catalyst in S5 is a nitrogen compound that catalyzes interfacial polycondensation reaction, preferably one or more of triethylamine, N-ethylpiperidine, and N-isopropylpiperidine; Preferably, the molar ratio of the catalyst to the compound containing bisphenol hydroxyl group is (0.002-0.004):1; And / or, the base in S5 is an alkaline hydroxide, preferably an alkali metal hydroxide, more preferably sodium hydroxide and / or potassium hydroxide; Preferably, the concentration of the alkali solution is 10wt%-50wt%, preferably 25wt%-35wt%; And / or, the temperature in S5 is 25-37° C., and the reaction time is 15-40 min.

9. The method according to claim 3, characterized in that: The cleaning in S6 is pickling and water washing; Preferably, pickling uses a strong acid; Preferably, the mass ratio of acid to oil phase during pickling is (0.1-0.5):1; And / or, the catalyst content in the solid product e in S6 is less than 1 ppm, the chloride ion content is less than 20 ppm, and the oily solvent content is less than 200 ppm.

10. The method according to claim 3, characterized in that: In the S7, the mold temperature is 240° C.-360° C., and the insulation time is 10 min-180 min.

11. A use of a scratch self-repairing polycarbonate, wherein the polycarbonate is the polycarbonate described in claim 1 or 2, or the polycarbonate prepared by the method described in any one of claims 3 to 10, and the polycarbonate is used for polycarbonate products that require scratch resistance and self-repairing, preferably for polycarbonate products in the fields of electronic products, automotive interiors, and optical lighting.

Citation Information

Patent Citations

  • Room-temperature self-repairing polycarbonate surface coating and preparation method thereof

    CN111548731A

  • Process for preparing polycarbonate

    CN101235136A

  • Aromatic sulphonate flame retardant compositions

    CN101384656A

  • Triazine derivative flame retardant with nitrogen-sulfur-silicon synergistic effect as well as preparation method and application of triazine derivative flame retardant

    CN111763352A

  • Method for preparing branched polycarbonate with continuous two-phase interface phosgene method

    US20160200864A1